(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Neonatal hyperbilirubinemia is one of the most common conditions requiring medical attention in the neonatal period. While most cases are physiological, delayed diagnosis and inappropriate management can lead to severe complications, including acute bilirubin encephalopathy and kernicterus. Aim & Objectives: To compare the clinico-etiological profile of neonatal hyperbilirubinemia between inborn and outborn neonates admitted to a tertiary care hospital and to identify key risk factors associated with pathological jaundice. Material & Methods: This hospital-based cross-sectional study was conducted in the Special Newborn Care Unit (SNCU) of a tertiary care hospital in Greater Noida over 12 months. Enrolled patients included 360 neonates ≤28 days with hyperbilirubinemia, either clinically suspected or biochemically confirmed. Data collection was done using a structured proforma, and etiological diagnosis was determined based on clinical and laboratory findings. Statistical analysis was done using SPSS v28.0; Chi-square and independent t-test were employed, with significance confirmed at p<0.05. Results: Of the 360 neonates included, 269 (74.7%) were inborn and 91 (25.3%) outborn. Pathological jaundice occurred more frequently among outborn neonates (60.4%) than inborn (28.6%) (p=0.001). In outborn infants, significantly higher prevalence for prematurity (36.1%), SGA status (56.1% vs 35.7%, p=0.002), and birth asphyxia (14.3% vs 4.8%, p=0.02) was observed. Neonatal sepsis was the most common etiology in outborn neonates (56.3%, p<0.001). On the other hand, ABO incompatibility (29.8%) and cephalohematoma (31.1%) were the principal factors among inborn infants. Total serum bilirubin levels were comparable between groups, though bilirubin testing was performed significantly earlier among inborn neonates (p=0.001). Conclusion: Significant differences exist in the etiological and clinical profile of hyperbilirubinemia between inborn and outborn neonates. Optimized early screening, infection control, and appropriate referral systems are mandatory in the reduction of preventable complications among outborn neonates.